Smart Learning Environments for Arabic Language Education: A Systematic Review for Generation Alpha Learners - Muhammad Syafii Tampubolon (Al-Jawhar : Journal of Arabic Language, 2025)
The rapid emergence of Generation Alpha as digital-native learners presents a fundamental challenge to traditional Arabic language pedagogy, which remains largely grammar-centered and teacher-directed. This mismatch highlights a critical gap between learners’ multimodal, interactive, and technology-driven preferences and existing instructional practices. This study aims to systematically examine the role of Smart Learning Environments (SLE) in transforming Arabic language education for Generation Alpha learners. Employing a Systematic Literature Review (SLR) approach, this research analyzes scholarly publications from the last decade indexed in major databases such as Scopus, ERIC, and Google Scholar, following PRISMA guidelines to ensure methodological rigor and transparency. The findings reveal that SLE frameworks encompassing artificial intelligence, gamification, and adaptive learning systems play a significant role in enhancing learner engagement, personalization, and interactivity. Furthermore, these technologies demonstrate measurable impacts across core Arabic language skills, including listening (istimā’), speaking (kalām), reading (qirā’ah), and writing (kitābah). The review also identifies a shift toward learner-centered and data-driven instructional models aligned with the cognitive and behavioral characteristics of Generation Alpha. This study concludes that the integration of Smart Learning Environments offers a transformative pathway for Arabic language education, making it more responsive, contextual, and effective. The findings provide important implications for curriculum development, pedagogical innovation, and future research in technology-enhanced Arabic language learning.